Implementation of Hand Movement Tracking for Real-Time Sign Language Translation - Bernardus Anggodho Aryudhawan Hadi; Wilfridus Bambang Triadi Handaya; Suyoto Suyoto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2026)
This study developed a real-time American Sign Language (ASL) sign language identification and interpretation system based on deep learning. The system used two data sources: the ASL alphabet dataset for individual character recognition and the WLASL dataset for vocabulary recognition. The WLASL dataset was chosen as the benchmark for evaluating complex word gestures because it encompasses a wide range of users and extensive movement dynamics. Data processing involved extracting hand-gesture and body-posture markers using MediaPipe, followed by preprocessing and augmentation. Two learning architectures were implemented: a Feedforward Neural Network for alphabet classification and a BiLSTM integrated with an Attention Mechanism for vocabulary recognition. The system was evaluated using accuracy, precision, recall, F1 Score, and K-fold cross-validation. The results demonstrated promising performance: 99% accuracy for alphabet recognition and 78% for vocabulary recognition, with the Attention Mechanism contributing substantially to vocabulary recognition. The system operates in real time at 15-20 FPS and is efficient on mid-range devices, potentially becoming an inclusive communication alternative for the sign language community.